Cryoablation of an Inguinal Angiomyomatous Hamartoma: A Case Report. Issue 7 (July 2021) - Woolley, Christopher A.; Gabriel, Rodney A.; Said, Engy T.; Chen, Jeffrey
Abstract : Angiomyomatous hamartomas are mixed-tissue benign lymphatic tumors that typically occur in the inguinal or axillary lymph nodes. These lesions may cause local lymphedema and painful compression neuralgias. Ultrasound-guided percutaneous cryoablation is an interventional technique that has been shown to provide sustained pain relief for peripheral neuropathies and neuralgias. Previously, our group published a case report of a patient with an inguinal angiomyomatous hamartoma causing a compression neuralgia, whose pain was temporarily alleviated after blockade of the femoral branch of the genitofemoral nerve. We present a follow-up case report describing this patient's sustained pain relief after cryoablation therapy.